Perceptions of Tap Water and School Water Fountains and Association With Intake of Plain Water and Sugar‐Sweetened Beverages. (March 2014) - Onufrak, Stephen J.; Park, Sohyun; Sharkey, Joseph R.; Merlo, Caitlin; Dean, Wesley R.; Sherry, Bettylou
ABSTRACT BACKGROUND Little is known regarding youth perceptions of tap water and school water fountains and how these relate to water and sugar‐sweetened beverage (SSB) intake. METHODS We used national 2010 YouthStyles data to assess perceptions of tap water and school water fountains and associations with water and SSB intake. RESULTS Nearly 1 in 5 participants disagreed their tap water was safe and nearly 2 in 5 disagreed school water fountains were clean and safe. Perceived tap water risk was more prevalent among non‐Hispanic (NH) Blacks (26.4%) and Hispanics (28.3%) compared with NH Whites (14.7%, p < .001) and more prevalent among lower‐income youth. Negative water fountain perceptions were more common among high school‐aged youth. Perceived tap water risk was not associated with SSB intake (odds ratio [OR] = 1.0, 95% confidence interval [CI]: 0.6, 1.5) or water intake (OR = 1.4, 95% CI: 0.9, 2.1). Negative water fountain perceptions were associated with SSB intake only among Hispanics (race/ethnicity interaction p < .001; OR = 2.9, 95% CI: 1.3, 6.6) but were not associated with water intake. CONCLUSION Negative perceptions of tap water and water fountains among youth are common and should be considered in efforts to provide water in schools.